TEMPORAL CHANGES IN CROP CONCENTRATION OF HARIDWAR DISTRICT - Kumar, Satayendra; Rai, Jyoti (International Journal of Research -GRANTHAALAYAH, 2020)
In the present paper cropping pattern in haridwar district is outlined, followed by the discussion on the area under individual crops. Jasbir singh’s method is used for concentration of selected crops. There has been a significant variation in the area patterns of the crop concentration in the study region. The indices of crop concentration area calculated from district statistical handbook 2000, 2005, 2010 and 2015, the crop concentration indices for all blocks of the district have been calculated for crops like paddy, wheat, oilseeds, maize, sugarcane, pulses. The spatial variations in the degree of crop concentration area are found to be the result of the different interaction such as physiographic, climatic, hydrological, socio-economic and technological factors in organizational of an area.